Microstructural characteristics of chitosan deposited az91 magnesium alloy. (2019) - Barani, B.; Lakshminarayanan, A.K.; Subashini, R.
Abstract: Magnesium (Mg) and its alloys have been extensively explored as potential temporary implant materials for orthopaedic applications (e.g. Fracture fixation). Magnesium alloy (AZ91) is used for bone implant application since it has lightest structural element, biocompatible, osteoconductive and its mechanical properties are similar to bone. However, they are prone to corrosion in the human body. Hence in order to reduce the corrosion rate and enhance the biocompatibility and biological properties, AZ91 magnesium alloy surface is modified with chitosan layers. Chitosan coating is proposed to decrease the corrosion rate and improve the bioactivity of AZ91 magnesium alloy. In the study, chitosan was coated on the surface of AZ91 magnesium alloy by spin coating technique. The presence of functional group bands of chitosan coating was confirmed using Fourier transform infrared spectroscopy (FTIR).The surface morphology and the grain size of chitosan on AZ91 magnesium alloy substrate was investigated using Field emission scanning electron microscope (FESEM) analysis. The elemental composition of chitosan was confirmed by Energy dispersive X-ray spectroscopy (EDAX) study. The film thickness was also measured for the coated substrate. Thus chitosan is coated on AZ91 magnesium alloy and characterization are done to confirm the presence of chitosan on AZ91 magnesium substrate which can be further tested for its biocompatible properties and used for orthopaedic applications.